Glenoid erosion is a risk factor for recurrent instability after Hill-Sachs remplissage. (1st April 2021) - Cavalier, Maxime; Johnston, Tyler Robert; Tran, Laurie; Gauci, Marc-Olivier; Boileau, Pascal
Abstract : Aims: The aim of this study was to identify risk factors for recurrent instability of the shoulder and assess the ability to return to sport in patients with engaging Hill-Sachs lesions treated with arthroscopic Bankart repair and Hill-Sachs remplissage (ABR-HSR). Methods: This retrospective study included 133 consecutive patients with a mean age of 30 years (14 to 69) who underwent ABR-HSR; 103 (77%) practiced sports before the instability of the shoulder. All had large/deep, engaging Hill-Sachs lesions (Calandra III). Patients were divided into two groups: A (n = 102) with minimal or no (< 10%) glenoid bone loss, and B (n = 31) with subcritical (10% to 20%) glenoid loss. A total of 19 patients (14%) had undergone a previous stabilization, which failed. The primary endpoint was recurrent instability, with a secondary outcome of the ability to return to sport. Results: At a mean follow-up of four years (1.0 to 8.25), ten patients (7.5%) had recurrent instability. Patients in group B had a significantly higher recurrence rate than those in group A (p = 0.001). Using a multivariate logistic regression, the presence of glenoid erosion of > 10% (odds ratio (OR) = 35.13 (95% confidence interval (CI) 8 to 149); p = 0.001) and age < 23 years (OR = 0.89 (0.79 to 0.99); p = 0.038) were associated with a higher risk of recurrent instability. A total of 80 patients (78%) could return to sport, but only 11 athletes (65%) who practiced high-risk (collision or contact-overhead) sports. All seven shoulders which were revised using a Latarjet procedure were stable at a mean final follow-up of 36 months (11 to 57) and returned to sports at the same level. Conclusion: Patients with subcritical glenoid bone loss (> 10%) and younger age (≤ 23 years) are at risk of failure and reoperation after ABR-HSR. Furthermore, following this procedure, one-third of athletes practicing high-risk sports are unable to return at their pre-instability level, despite having a stable shoulder. Cite this article: Bone Joint J  2021;103-B(4):718–724.